Induction of stigma-like structures in saffron (Crocus sativus L.): Exploring factors and metabolite analysis - Parvaneh Mahmoudi; Ahmad Moieni; Mojtaba Khayam Nekouei; Mohsen Mardi; Ghasem Hosseini Salekdeh (PLoS ONE, 2025)
Saffron (Crocus sativus L.) has held significant cultural and medicinal value since the Greek-Minoan civilization. As a triploid spice with vegetative propagation from the Iridaceae family, the three-branch style of C. sativus flowers, known as saffron, constitutes the most economically valuable part of the plant, renowned for its diverse medicinal properties. This study explores the in vitro induction of stigma-like structures (SLSs) from various explants of the Ghaen ecotype flower. The study found that the optimal sampling time for the majority of explants was the third week of October. Ovary explants exhibiting a prolonged response to hormonal treatments for the production of SLSs. Furthermore, intact, and injury ovary explants were found to be the most effective explant types for inducing SLSs. The explants were cultured on MS, 1/2MS, LS and B5 basal media supplemented with various combinations and concentrations of plant growth regulators. The results indicated that the B5 medium, enriched with 5–10 mg/ L BAP and 5–10 mg/ L NAA was the most effective treatment for inducing SLSs in all types of explants. Quantitative and qualitative analyses of saffron compounds in SLSs indicated similarities with natural saffron, albeit at significant lower concentrations: crocin (up to 10.2 mg/g), picrocrocin (up to 4.8 mg/g), and safranal (up to 9.7 mg/g). The highest accumulation of the three studied secondary metabolites was observed in the SLSs of style (24.4 mg/g), stigma (28.3 mg/g), and ovary (21.4 mg/g) explants, respectively. This study introduces a comprehensive procedure for producing SLSs containing the three most important metabolites of saffron for the first time.